The Role of School Libraries in Improving Information Literacy in Children: A Systematic Literature Review - Firmansyah, Ali; Alaauddin, Akmal Insan (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
Libraries are considered important to be able to manage, organize, store and collect collections of library materials systematically which are used as a source of information by users. The school library is a place of information especially for students, teachers and other school members. Through information literacy students will be able to learn independently, because it involves recognising when information is needed and being able to efficiently search, accurately evaluate, effectively use, and clearly communicate. The research method used was systematic literature review (SLR) and researchers conducted a literature search using the Publish or Perish (PoP) application using the Google Scholar database by reviewing with a search strategy using the keywords "school library AND children's information literacy", which were published in the last 3 years (2022-2024). The number of literature analyzed in this study was five. The results showed that the library always provides programmes that are used as innovations to increase the level of information literacy in children, not only that the role of parents and the surrounding environment also contributes to the success of these programmes.